The superiority of midazolam-pethidine combination in three different anesthetic methods applied in conscious sedation during transesophageal echocardiography procedure - Yilmaz AK, Hulya; Ozsahin, Yasemin; Yesiltas, Mehmet Ali; Arslan, Sukru; Bostan, Cem; Haberal, İsmail; Yildiz, Mustafa (Asian Journal of Medical Sciences, 2022)
Background: During the transesophageal echocardiography (TEE) procedure, as in many other diagnostic semi-invasive applications, moderate sedation is preferred over deep sedation. Rarely, patients who cannot tolerate moderate sedation may require deep sedation when difficulties are encountered during TEE probe insertion. Although many different methods have been tried for the TEE procedure in clinical practice, the most appropriate sedation method is still controversial. Aims and Objectives: We aimed to evaluate the clinical effects of three different sedoanalgesia methods consisting of midazolam, propofol, and midazolam-pethidine combination protocols applied for conscious sedation in the patients undergoing a TEE procedure, and to evaluate the patient and doctor satisfaction during the procedure. Materials and Methods: One-hundred twenty five patients who underwent TEE for diagnostic purposes in our hospital were included consecutively in our prospective randomized trial. The patients were divided into three groups as those who were administered midazolam (group M), propofol (group Pr), and midazolam-pethidine (group MPe) during the TEE procedure. Results: In the MPe group, both patient and doctor satisfaction were significantly higher than the two groups. The rate of difficulty in probe placement was lower in the Pr and MPe groups compared to the M group (P<0.05). Conclusion: In this study, it has been observed that conscious sedation with the combination of midazolam-pethidine was significantly advantageous in terms of patient and physician satisfaction compared to the use of only midazolam and only propofol.